Kinerja keuangan perusahaan pada saat pandemi covid-19 dan saat pemulihan pasca pandemi covid-19 - Mandavani, Tufahati Ainia; Prasetyo, Tri Joko; Putri, Widya Rizki Eka (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The phenomenon of the Covid-19 pandemic has caused changes in life and economic activities. Based on the Statistical Indicators Sub-Directorate Survey by the Central Bureau of Statistics (BPS) Sub-Directorate of Statistics Survey regarding the impact of Covid-19 on business actors conducted in July 2020, it was stated that the majority of companies affected by Covid-19 were 82.85% of companies experiencing decrease in income, while 14.6% of other companies still get the same income from before covid-19. This research aims to determine the difference between CR, DAR, ROA, TATO on the company's financial performance during the COVID-19 pandemic and during recovery after the COVID-19 pandemic. This type of research is quantitative with secondary data collection from the financial statements of 2020 and financial statements of 2021. Sampling uses the purposive sampling method and the samples in this study are 96 companies in the infrastructure, utility, and transportation sectors listed on the IDX in 2020 and 2021. Normality test In this study using the Kolmogorov-Smirnov test and it was concluded that the data that were normally distributed were using the paired sample t-test and the data were not normally distributed. The non-parametric Wilcoxon signed rank test was used. The results of this study indicate that there are differences in CR, ROA, and TATO during the covid-19 pandemic and during recovery after the covid-19 pandemic, and there is no difference in DAR during the covid-19 pandemic and during recovery after the covid-19 pandemic.